Leksykograficzne wędrówki pąci i peregrynacji - Jolanta Migdał (Annales Universitatis Paedagogicae Cracoviensis. Studia Linguistica, 2018)
The article presents a lexicographical history of two word families: pąć and peregrynacja. It has been demonstrated how these families evolved quantitatively at various periods of the development of the Polish language, how the semantics of lexemes functioning in these aggregates changed. The analysed material has been excerpted from historical and modern general language dictionaries and etymological dictionaries of Polish as well as from expert publications in the field of religious studies.